Experimental Studies to Validate Computational Fluid Simulation of Coolant Flow Behavior through different Nozzles for Nozzle Effectiveness in Cylindrical Grinding Process to Enhance Workpiece Surface Quality - Singh, Mandeep; Sharma, Yadwinderpal; Singh, Jaskarn (Asian Journal of Engineering and Applied Technology, 2016)
In the present paper, ANOVA (Analysis of Variance) technique has been adopted. The simulated results of flow behaviour through six different kinds of nozzles were experimentally validated to study the effect of these different types of nozzles as well as other process parameters on the response parameter namely surface roughness of ground workpiece during a cylindrical grinding process and optimized using this technique. The air flow behaviour around the rotating wheel and workpiece was simulated with computational fluid approach in ANSYS CFX. The optimum solution was found coherent with the simulated results. Spline type nozzle followed by convergent-divergent type was found the two best nozzles. Optimized solution also indicated the best parametric setting for the optimum results.